(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Metacognition, mostly identified as the special skill to represent on and intellectually supports university applicants own thinking processes, plays a essential role ineducational atteinment. This article investigates that the theoretical definitions of metacognition and examines its relationship with academic achievement in educational contexts. Drawing on key cognitive and educational psychology research, the study discusses core components of metacognition, including planning, monitoring, and evaluation, and highlights how these processes contribute to effective learning and self-regulated behavior. The article further reviews empirical evidence demonstrating that students who actively employ metacognitive strategies tend to perform better academically, exhibit greater learning autonomy, and adapt more effectively to complex academic tasks. Additionally, the paper agrees with instructional approaches for encouraging metacognitive skills in classroom conditions and tackles challenges related to assessment and enactment. The findings underscore the importance of integrating metacognitive instruction into educational practice to enhance learning outcomes and promote long-term academic development.